Psychological value of time - Eugenia Dengo Obregón, María (2005)
In order to reflect on the significance of time, different approaches can be adopted. From the simple meteorological, that the whole does not correspond with this opportunity, to the philosophical or the historical, that analyzes the time, considered as the course of human history, the inclusive one can adopt the geological approach, that of the history of the ages of the earth, and even the universe